2015
DOI: 10.1186/s13014-015-0570-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of morphometric atlas selection on multi-atlas-based automatic brachial plexus segmentation

Abstract: PurposeThe present study aimed to measure the effect of a morphometric atlas selection strategy on the accuracy of multi-atlas-based BP autosegmentation using the commercially available software package ADMIRE® and to determine the optimal number of selected atlases to use. Autosegmentation accuracy was measured by comparing all generated automatic BP segmentations with anatomically validated gold standard segmentations that were developed using cadavers.Materials and methodsTwelve cadaver computed tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Schipaanboord et al 48 and Van de Velde et al 49 both showed that when atlas selection strategies are used to select atlases most similar to the anatomy of the patient being segmented, performance is significantly improved over using a random selection of atlases. This concept can logically be extended to support the IPP atlas-based autosegmentation method used in the current paper; using prior images from the same patient as atlases achieves the maximal similarity between the atlases and the image being segmented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schipaanboord et al 48 and Van de Velde et al 49 both showed that when atlas selection strategies are used to select atlases most similar to the anatomy of the patient being segmented, performance is significantly improved over using a random selection of atlases. This concept can logically be extended to support the IPP atlas-based autosegmentation method used in the current paper; using prior images from the same patient as atlases achieves the maximal similarity between the atlases and the image being segmented.…”
Section: Discussionmentioning
confidence: 99%
“…Schipaanboord et al 48 . and Van de Velde et al 49 . both showed that when atlas selection strategies are used to select atlases most similar to the anatomy of the patient being segmented, performance is significantly improved over using a random selection of atlases.…”
Section: Discussionmentioning
confidence: 99%
“…Schipaanboord et al [46] and Van de Velde et al [47] both showed that when atlas selection strategies are used to select atlases most similar to the anatomy of the patient being segmented, performance is significantly improved over using a random selection of atlases. This concept can logically be extended to support the IPP atlas-based autosegmentation method used in the current paper; using prior images from the same patient as atlases achieves the maximal similarity between the atlases and the image being segmented.…”
Section: Discussionmentioning
confidence: 99%